Práticas de apoio na atenção primária : um SUS que produz veredas - Valencio, Rafael Dias (2018)
The Unified Health System is presented in the Federal Constitution of 1988, through the law 8080/90, as a health policy that is universal in the access, equanimity in the attention and integral in the care. Through the law 8142/90 is guaranteed, in legal terms, the social control in the construction of the SUS. There is, thus, a legal apparatus of guarantee of right and promotion of the health policy constitutionally guaranteed. Despite of the legislations, ordinances and resolutions, the operationalization of a health policy doesn’t occur in a legal sphere, but in the daily of the services, in the relationship between workers and users. This research brings narratives of experience in NASF of Santa Teresa/ES, the mode how institutional and matrix support practices have been developed, in the fomentation of a health policy that is made public and, thus, collective. Throughout the text we will see how the support work developed by the NASF seeks to direct practices that promote collectivity and health, this understood as a normative activity. Thereby, this text is divided in three parts: The first paths, a moment we are narrating how comes the interest in this research as well the way that the Santa Teresa/ES work team began to be constituted, understanding the NASF as a device and the work tools that we resort; the concepts of health as normative activity and what we call institutional support and matrix support; and we present the intercessors (expanded clinic, network production, territories) that guided the planning and the support activities. The daily meetings in the health services direct us to a experimentation of the SUS that increases the potency of action, that builds paths. In this sense, the practice of support brings a new working arrangement that allows strengthening of links, creation of new existential territories, and enlargement of the capacity of action for health production. We think, together with workers and users, a health practice that produces new ways, new ways of working, sharing knowledges and practices, sharing life, creating paths.